A survey of classroom practices of novice male and female Malaysian teachers in teaching the literature in English component / Mohd Nur Fitri Mohd Salim - Mohd Salim, Mohd Nur Fitri (2014)
This study was conducted with the aim to identify the teaching approaches and teaching activities employed by male and female novice teachers in teaching LIE component. This survey research comprised 8 secondary novice teachers (4 male and 4 female) and 200 students from 4 different schools in Kajang, Selangor. The study employed a mixed-methods research design where data were collected using a questionnaire and semi-structured interviews. The quantitative data of this study was analyzed statistically using SPSS while the qualitative data was analyzed based on the research questions and served to triangulate the results. The findings of this study revealed that the approach that was most preferred by novice teachers in teaching LIE was Moral-Philosophical Approach (Mean= 4.16) and the least preferred approach was Stylistic Approach (Mean= 3.53). For teaching activities, findings showed that novice teachers preferred to use Language-Based activities in teaching LIE component (Mean=4.16). Findings also indicated that there was a significant difference in the mean scores between male and female novice teachers in their preferences of teaching approach and teaching activities in teaching LIE component. However, findings gathered from the novice teachers were in contrast with the findings gathered from the students. Based from the questionnaire given to the students, findings showed that students prefer their teachers to use Language-Based Approach and Personal-Response activities in learning LIE component. Findings also showed that the two common challenges faced by novice teachers in teaching LIE component were students' lack of interest and students' proficiency level. The findings also imply that novice teachers should be given more training in order to improve their teaching and expose them to the best teaching approaches and teaching activities in teaching LIE component.